2011
DOI: 10.1016/j.febslet.2011.08.039
|View full text |Cite
|
Sign up to set email alerts
|

MiR-483-5p controls angiogenesis in vitro and targets serum response factor

Abstract: Edited by Tamas DalmayKeywords: miRNA Ischemic Heart disease IGF2 Angiogenesis SRF a b s t r a c t Angiogenesis, a key factor in ischemic heart disease, is rapidly initiated in response to hypoxic or ischemic conditions. MicroRNAs (miRNAs) are endogenously expressed small non-coding RNAs that regulate gene expression at post-transcriptional level. The recent discovery of the involvement of these RNAs in the control of angiogenesis renders them very attractive in the development of new approaches for restoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…MiR‐483‐5p is down‐regulated under hypoxia condition and can inhibit the growth of HUVECs by targeting serum response factor (SRF), which recedes wound healing and tube formation 110. Consistent with this, Kong et al111 found miR‐483‐3p can inhibit angiogenesis, up‐regulated in EPCs of DVT patients, which can inhibit EPC migration and tube formation and enhance apoptosis in vitro by targeting SRF, thus, reducing EPC homing and thrombus organization and recanalization in rat inferior vena cava thrombosis model.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…MiR‐483‐5p is down‐regulated under hypoxia condition and can inhibit the growth of HUVECs by targeting serum response factor (SRF), which recedes wound healing and tube formation 110. Consistent with this, Kong et al111 found miR‐483‐3p can inhibit angiogenesis, up‐regulated in EPCs of DVT patients, which can inhibit EPC migration and tube formation and enhance apoptosis in vitro by targeting SRF, thus, reducing EPC homing and thrombus organization and recanalization in rat inferior vena cava thrombosis model.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…It is also known that Igf2 enables Myod to activate its target genes by acting on the recruitment of Myod co-activators (Polesskaya et al, 2001). More recently, the Srf transcription factor has been shown to be a direct target of miR-483-5p, the gene for which is embedded in intron 2 of Igf2 (Qiao et al, 2011). Srf is one of the factors responsible for the activation of Myod expression.…”
Section: Myodmentioning
confidence: 99%
“…Development 140 (6) Srf was recently shown to be a direct target of miR-483 (Qiao et al, 2011) and is known to be a direct regulator of Myod expression. We confirmed by ChIP assay on whole limb muscle tissue that Srf binds to the Myod CArG box (Fig.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…32 miR483-5p, miR500 and miR576-3p are involved in the processes of angiogenesis, cell cycle and immune response. 33 Our data raise the questions of whether the sustained over-expression of these miRNA induced by G-CSF could lead to modifications in any of these biological processes and whether or not this has any clinical implication.On the other hand, G-CSF produced changes in proteinencoding gene expression levels at all time-points analyzed during the follow up. In our study we identified 617 genes with a greater modification in their expression levels after treatment.…”
mentioning
confidence: 99%